2014
DOI: 10.1016/j.coph.2014.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine-disrupting actions of PCBs on brain development and social and reproductive behaviors

Abstract: Polychlorinated biphenyls are among the most well-studied endocrine-disrupting chemicals (EDCs) for their neurobehavioral effects, especially neurodevelopment and cognitive performance. In addition, past research has demonstrated effects of PCBs on circulating hormones and associated changes in reproductive behaviors. This article will focus on recent advances that have been made in characterizing developmental PCB effects on reproductive function, broader social and affective behaviors, and the neuroendocrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 101 publications
0
53
0
Order By: Relevance
“…Although their production in the United States was banned in the 1970s and their use today is highly controlled, PCBs persist in the environment and accumulate in the food web (Bell 2014; Fernandez-Gonzalez et al 2015). Different PCB congeners have been associated with reproductive dysfunction in females.…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%
“…Although their production in the United States was banned in the 1970s and their use today is highly controlled, PCBs persist in the environment and accumulate in the food web (Bell 2014; Fernandez-Gonzalez et al 2015). Different PCB congeners have been associated with reproductive dysfunction in females.…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%
“…Numerous studies have demonstrated a relationship between PCBs exposure and a variety of toxic effects, such as carcinogenicity, teratogenicity or reproductive toxicology in animals (Bell, 2014;El Majidi et al, 2014;Zani et al, 2013). Also, correlation between environmental and occupational exposures to PCBs and human prostate cancer has been reported (Kling et al, 1978;Hessel et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Numerous modes of action have been described that may contribute to neurotoxicity. This includes altered neurotransmitter signaling (Fonnum and Mariussen, 2009;Mariussen and Fonnum, 2001;Wigestrand et al, 2013), altered GABA A receptor activity (Fernandes et al, 2010), altered Ca 2þ homeostasis through several mechanisms (Choi et al, 2016;Gafni et al, 2004;Kodavanti and Tilson, 1997;Pessah et al, 2010;Westerink, 2014), induced reactive oxygen species (Stenberg et al, 2011), altered cell viability (Dickerson et al, 2009), and alterations of neuro/endocrine processes (Bell, 2014;Fonnum and Mariussen, 2009;Kodavanti and Curras-Collazo, 2010). Of the modes identified, a particularly sensitive endpoint is the ability of NDL PCBs to enhance the activity of ryanodine sensitive Ca 2þ channels embedded in the sarco/endoplasmic reticulum (SR/ER), namely, the ryanodine receptor (RyR), in both mammals (Pessah et al, 2006) and fish (Fritsch and Pessah, 2013).…”
mentioning
confidence: 99%